Ethnography And Problems Of Islamic Education In The Community Of West Papua-Papua - Muhammad Rizal Fadli; Fitri Siyami; Habibah Habibah; Mardiah Bachmid; Indria Nur (Educare: Journal Educational and Multimedia, 2024)
The indigenous Papuan Muslim community until now is famous as a community that embraces minority religions. So in some places, they seem to be isolated and get less attention. There is a fairly close relationship between ethnography and society and culture as a result of its creativity. Therefore, this relationship needs to be applied positively, where it is necessary to use ethnographic studies as an alternative form in carrying out research on culture in society. The problem of education is also one of the important problems that must be solved and know the cause and effect of the educational problem.